Methodological problems of using questions in foreign language teaching - Iluk, Jan (Glottodidactica, 2018)
The author discusses the status and role of questions in foreign language teaching. Although they are essential tools of managing the learning process, the topic does not enjoy much interest in the methodological literature. Therefore it seems advisable to discuss the methodological problems of foreign language teaching in a broader context including both the activation of learners and teachers with questions and application of questions while working with a foreign language text